THE ROLE OF FAMILYNIG IN PREPARING A CHILD FOR SCHOOL EDUCATION - Zakirova Mukhabbat Sabirovna (Bright Mind Publishing, 2025)
This article covers the psychological foundations of the preparation of preschool children for school education and the role of the family in this, analyzes the studies carried out in this regard.
Keywords: School education, intellectual, physical, moral, fine motorics, competence.